A survey of preparedness against coronavirus disease 2019 (COVID-19) in hospitals in Tokyo, Japan, with healthcare personnel with COVID-19 and in-facility transmission. (29th June 2021) - Tagashira, Yasuaki; Takamatsu, Akane; Hasegawa, Shinya; Uenoyama, Yuki; Honda, Hitoshi
Abstract: A questionnaire was distributed to hospitals in Tokyo (N = 38) regarding their preparedness against and in-facility transmission of coronavirus disease 2019 (COVID-19). As of May 31, 2020, 284 HCP had contracted COVID-19, and in-facility COVID-19 transmission occurred at 13 hospitals, negatively impacting hospital functions and patient care.